2017
DOI: 10.1186/s13075-017-1288-y
|View full text |Cite
|
Sign up to set email alerts
|

Calgizzarin (S100A11): a novel inflammatory mediator associated with disease activity of rheumatoid arthritis

Abstract: BackgroundCalgizzarin (S100A11) is a member of the S100 protein family that acts in different tumors by regulating a number of biologic functions. Recent data suggest its association with low-grade inflammation in osteoarthritis (OA). The aim of our study is to compare S100A11 expression in the synovial tissues, synovial fluid and serum of patients with rheumatoid arthritis (RA) and osteoarthritis (OA) and to characterize the potential association between S100A11 and disease activity.MethodsS100A11 protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…The three top markers common to old cells were the genes Aw112010 , S100a11 , and Izumo1r (AUC > 0.66 and power > 0.33; Fig. 1G), which were recently reported to be up-regulated under chronic inflammatory conditions ( 23 25 ). These genes imply a strong relationship between the inflammatory state and the identity of CD4 T cells in aging and can be used as general markers for aged CD4 T cells.…”
Section: Resultsmentioning
confidence: 86%
“…The three top markers common to old cells were the genes Aw112010 , S100a11 , and Izumo1r (AUC > 0.66 and power > 0.33; Fig. 1G), which were recently reported to be up-regulated under chronic inflammatory conditions ( 23 25 ). These genes imply a strong relationship between the inflammatory state and the identity of CD4 T cells in aging and can be used as general markers for aged CD4 T cells.…”
Section: Resultsmentioning
confidence: 86%
“…ADH1C protein is involved in alcohol metabolism and associated with alcohol dependence [ 22 , 32 ]. S100A11 belongs to the S100 protein family and is a known inflammatory factor [ 33 ]. SERPINC1 is a member of the serpin superfamily and a plasma protease inhibitor; it inhibits thrombin and acts as an anti-inflammatory factor [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…S100A11, also known as S100C or calgizzarin, has been reported to contribute to inflammatory processes [ 42 ] and multiple neoplastic events in different types of cancers, including papillary thyroid cancer [ 43 ], ovarian cancer [ 44 ], cholangiocarcinoma [ 45 ], pancreatic carcinoma [ 46 , 47 ] and gastric cancer [ 48 ]. Takamatsu et al concluded that extracellular S100A11 contributes significantly to the spread of the fibroblast population in pancreatic cancer, thus becoming a potential therapeutic target [ 49 ].…”
Section: Discussionmentioning
confidence: 99%